2020
DOI: 10.1007/s40121-020-00341-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Good Patient Outcomes Following Convalescent Plasma in COVID-19: A Prospective Phase II Clinical Trial

Abstract: Introduction: Coronavirus disease 2019 (COVID-19) is a viral respiratory syndrome caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This novel virus was discovered in Wuhan City, Hubei Province, China, in December 2019. As of September 6, 2020, confirmed cases have risen to more than 27,000,000 worldwide and more than 885,000 people have died. Currently, no cure or standard treatment for COVID-19 exists. We conducted a prospective single-arm open-label phase II clinical trial assessing th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…Patients treated early had a lower mortality rate and shorter hospital admission. Convalescent plasma infusion caused no adverse effects ( 72 ).…”
Section: Clinical Findings: a Glance From The Specialistsmentioning
confidence: 97%
“…Patients treated early had a lower mortality rate and shorter hospital admission. Convalescent plasma infusion caused no adverse effects ( 72 ).…”
Section: Clinical Findings: a Glance From The Specialistsmentioning
confidence: 97%
“…Limited previous clinical experiences with CP treatment in SARS-CoV, MERS, influenza, and Ebola suggest that CP may provide benefits to COVID-19 patients (Bloch et al, 2020;Devasenapathy et al, 2020). Many recent reports have documented clinical outcomes of CP treatment in severe and critically ill COVID-19 patients (Ahn et al, 2020;Ibrahim et al, 2020;Jin et al, 2020;Keith et al, 2020;Li et al, 2020a;Li et al, 2020b;Liu et al, 2020a;Madariaga et al, 2020;Maor et al, 2020;Pei et al, 2020;Perotti et al, 2020;Dwi Putera and Suci Hardianti, 2020;Shen et al, 2020a;Wang et al, 2020c;Ye et al, 2020a;Zhang et al, 2020a). Two categories of results are presented.…”
Section: Convalescent Plasma and Ivig Treatment Of Covid-19 Patientsmentioning
confidence: 99%
“…Among the above studies, 11 reported CP treatment in 10 or less COVID-19 patients (Ahn et al, 2020;Duan et al, 2020;Jin et al, 2020;Keith et al, 2020;Li et al, 2020a;Madariaga et al, 2020;Pei et al, 2020;Shen et al, 2020a;Wang et al, 2020c;Ye et al, 2020a;Zhang et al, 2020a). Five studies treated 37-49 patients (Ibrahim et al, 2020;Liu et al, 2020a;Maor et al, 2020;Perotti et al, 2020;Dwi Putera and Suci Hardianti, 2020). Only one randomized trial wherein 52 patients received CP treatment was reported and the results demonstrated that CP therapy plus standard treatment in severe or life-threatening COVID-19 patients did not result in significant clinical improvement (Li et al, 2020b).…”
Section: Convalescent Plasma and Ivig Treatment Of Covid-19 Patientsmentioning
confidence: 99%
“…Also, a similarly designed study in India [16] in a much larger group of patients showed only a limited survival benefit, although many patients with non-critical conditions experienced improved symptoms and oxygenation, and faster viral clearance relative to controls. A serious limitation of the latter study was the relatively low antibody titers (1:20-1:40) of the transferred plasma, which were much lower than in the Wuhan and Hartford studies [ 2 , 14 ].…”
Section: Passive Immunization For Covid-19mentioning
confidence: 83%
“…No severe adverse effects were observed. Similarly, in a small clinical trial involving 38 patients in Hartford, CT, convalescent plasma was well tolerated, and there was moderate benefit [14] .…”
Section: Passive Immunization For Covid-19mentioning
confidence: 90%